Gas exchanges in grapevines under water stress regime. II. Photorespiration and varietal behavior - Regina, Murillo de Albuquerque; Carbonneau, Alain (Pesquisa Agropecuaria Brasileira, 1999)
The photorespiration in grapevines (Vitis vinifera L.) leaves subjected to a water stress regime was analysed with the purpose of characterizing the behavior of different cultivars. Two-year old plants were used, grafted on Fercal, planted in plastic pots and cultivated in controlled environment. The photorespiration was calculated from leaf gas exchange measurements taken by means of a portable infrared CO2 analyser (LCA3-ADC), working in an open circuit. The absolute photorespiration values varied little among cultivars and level of irrigation, whereas the carboxylation efficiency and the CO2 compensation point were highly affected by the water stress, thereby evidencing different varietal sensitivity levels. The occurrence of a nonstomatal inhibition of the photosynthesis was verified affecting in a specific way the cultivars analysed. The Chardonnay adapted itself better to the water stress conditions as opposed to the high sensitivity on the part of Sémillon and Ugni blanc.